Demographic Aspects of Scheduled Caste and Scheduled Tribe in Different Agro-c1imatic Regions of Western Rajasthan - Gupta, B S; Chand, Roop (Annals of Arid Zone, 2025)
A substantial portion of Rajasthan’s population consists of scheduled caste and scheduled tribe. They were 76,07,820 and 54,74,881, which formed 17.29 and 12.44% during 1991. But in the case of western Rajasthan, the scheduled. caste and scheduled tribe population to total population was 18.93 and 2.52%, respectively. The scheduled castes and scheduled tribe together contributed 21.45% to the total population in western Rajasthan. The density of population, the decennial growth rate of scheduled caste and scheduled tribe in different arid districts lagroclimatic regions are dealt with. Jhunnhunu highest scheduled caste population density (41), whereas .Jaisalmer has minimum population density (1). In the entire western Rajasthan, the density of tribal population was highest in Jalor 9.1 and lowest in Bikaner 0.1. The density of population of scheduled caste and scheduled tribe in western Rajasthan during 1981 was 12.0 and 1.6 persons km-2 which became 15.9 and 2.1 persons km-2 during 1991. Working population of scheduled caste and scheduled tribe and proportion of main workers, marginal workers to total population in different agro-climatic regions have been dealt with.